Building a Sustainable Maritime Finance Ecosystem: Enhancing Shipping Management and Education - Wibowo, Titis Ari; Mudakir , Mudakir; Hamzah, Muhammad Zilal; Sofilda, Eleonora (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
This research explores the intersection of maritime finance, sustainability, and education, aiming to develop a sustainable maritime finance ecosystem. Focusing on port and shipping management, the study examines the perspectives of three key stakeholder groups: maritime industry experts, educators, and graduates. Through qualitative research and descriptive analysis, the study identifies key challenges and opportunities in aligning financial practices with sustainability goals. Findings show that while industry professionals and educators recognize the importance of green finance and sustainable business practices, gaps remain in education, particularly in integrating up-to-date sustainability principles into curricula. Furthermore, the research emphasizes the need for continued collaboration between industry, education, and policy to ensure that future maritime professionals are equipped with the skills necessary to navigate evolving financial and environmental challenges. The results provide actionable insights for enhancing vocational training and curriculum development to support the maritime sector’s transition to more sustainable and financially viable practices. Overall, this research highlights the crucial role of education in fostering a sustainable maritime future and provides recommendations for improving maritime finance and sustainability frameworks.